Sensitivity and specificity of meningeal signs in patients with meningitis. (15th July 2019) - Akaishi, Tetsuya; Kobayashi, Junpei; Abe, Michiaki; Ishizawa, Kota; Nakashima, Ichiro; Aoki, Masashi; Ishii, Tadashi
Abstract: Background: Several types of physical examinations are used in the diagnosis of meningitis, including nuchal rigidity, jolt accentuation, Kernig's sign, and Brudzinski's sign. Jolt accentuation was reported to have sensitivity of nearly 100% and to be highly efficient for excluding meningitis, but more recent studies showed that a number of patients with meningitis may present negative in this test. Methods: We systematically reviewed studies on the above‐mentioned physical examination tests and performed meta‐analysis of their diagnostic characteristics to evaluate the clinical usefulness. Nine studies, comprising a total of 599 patients with pleocytosis in the cerebrospinal fluid (CSF) and 1216 patients without CSF pleocytosis, were enrolled in the analysis. Results: Jolt accentuation showed a decent level of odds ratio (3.62; 99% confidence interval (CI): 1.13‐11.60, P  = 0.004) comparable to that in nuchal rigidity (2.52; 1.21‐5.27, P  = 0.001) for the correct prediction of CSF pleocytosis among subjects with suspected meningitis. The estimated sensitivity was relatively high (40%‐60%) in nuchal rigidity or jolt accentuation tests. On the other hand, Kernig's and Brudzinski's signs exhibited relatively low sensitivity (20%‐30%). The estimated specificity was higher in Kernig's and Brudzinski's signs (85%‐95%) than in nuchal rigidity or jolt accentuation tests (65%‐75%). Conclusion: Approximately half of the patients with meningitis may not present typical meningeal signs upon physical examination. Combining several examinations for the detection of meningeal signs may decrease the risk of misdiagnosis. Abstract : Nuchal rigidity and jolt accentuation showed similar sensitivity, specificity, and odds ratio in diagnosing meningitis. The estimated sensitivity of nuchal rigidity and jolt accentuation was 40%‐60%. Clinicians need to remember that nearly half of the patients with meningitis may not show meningeal signs.